2016
DOI: 10.5352/jls.2016.26.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of MLO Family Genes under Podosphaera xanthii Infection and Exogenous Application of Phytohormones in Cucumis melo L.

Abstract: Powdery mildew disease caused by Podosphaera xanthii is a major concern for Cucumis melo production worldwide. Knowledge on genetic behavior of the related genes and their modulating phytohormones often offer the most efficient approach to develop resistance against different diseases. Mildew Resistance Locus O (MLO) genes encode proteins with seven transmembrane domains that have significant function in plant resistance to powdery mildew fungus. We collected 14 MLO genes from 'Melonomics' database. Multiple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…The results indicated that at least one dominant allele is required in LG XII in presence of homozygous dominant status of LG II locus (Table 7). In a recent study, differential expression of 14 MLO genes have been reported in the same melon line in response to seven different fungal races of P. xanthii (Howlader et al 2016) which suggested possible existence of inter-genic gene interaction.…”
Section: Epistatic Gene Interaction Is Presentmentioning
confidence: 96%
“…The results indicated that at least one dominant allele is required in LG XII in presence of homozygous dominant status of LG II locus (Table 7). In a recent study, differential expression of 14 MLO genes have been reported in the same melon line in response to seven different fungal races of P. xanthii (Howlader et al 2016) which suggested possible existence of inter-genic gene interaction.…”
Section: Epistatic Gene Interaction Is Presentmentioning
confidence: 96%
“…As Howlader et al . 25 reported, MLO genes have different expression patterns after being infected by powdery mildew bacteria, and some are up-regulated and down-regulated. It is difficult to say that TG-1 resistance or TG-5 susceptibility is related to these differentially expressed MLO genes.…”
Section: Discussionmentioning
confidence: 99%
“…Howlader et al . reported the expression of 14 CmMLO genes after infection of Melon with seven different races of P. xanthii 25 .…”
Section: Introductionmentioning
confidence: 99%